PERBEDAAN TERAPI PIJAT AKUPRESUR DAN BREASTCARE TERHADAP PENGELUARAN ASI PADA IBU POSTPARTUM - Nurhasanah, Siti; Masluroh, Masluroh (NHM PRESS, 2022)
Acupressure massage and breast care is one way to increase milk production. The purpose of this research is to know the difference between acupressure massage therapy and breastcare on the release of breast milk in postpartum mothers at PMB S.H Panongan, Tangerang Regency, Banten. This research method is a quasi-experimental using a pretest and posttest with control group design. The sample in this study amounted to 30 postpartum mothers 1-4 days in February-April 2022 who gave birth at PMB S.H Panongan Tangerang Regency Banten with 15 respondents in each group. The sampling technique is total sampling. The research instrument used an observation sheet of 7 indicators of the smooth flow of breast milk. The data were analyzed using an independent T-test which had previously been tested for normality and homogeneity. The results of the study of breast milk production before receiving acupressure massage therapy were mostly not smooth as much as 86.7% and afterward most of them were smooth as much as 93.3%. Expenditure of breast milk before getting breastcare was mostly not smooth as much as 86.7% and after that mostly smooth as much as 80.0%. There is a difference between acupressure massage therapy and breastcare on the ejection of breast milk in postpartum mothers with a significance level of 0.007. The conclusion is that giving acupressure massage therapy is more effective in removing breast milk in postpartum mothers than breast care.